The "resurrection" of industrial policy in the European Union and its impact on industrial policy in the New Member Countries - Ádám Török; Gyöngyi Csuka; Bernadett Kovács; Anita Veres (WWWforEurope, 2013)
The aim of this study is to consider the main factors affecting the industrial policy in Central and Eastern European Countries (CEECs) by elucidating the issues such as; the connection between competitiveness and industrial policy, innovation, manufacturing, green growth and environment. The objective is to inspire thought in the reader and to highlight the necessity for a new industrial policy, which considers regional differences and specializations in the catching up economies of the CEECs. The ultimate question is what kind of industrial policy development is required in the CEECs in the future that could enable an even more successful catching up, or convergence, with the Western economies. This study includes an analysis of the countries that have been more successful in transition. A measurement was made of the export market shares as well as the industrial structure (primarily in manufacturing). The first step towards accomplishing this task was to examine the export competitiveness of CEECs, the concept of export competitiveness, and the role of exports in competitiveness-oriented growth strategies during the financial crisis. The question was how the effectiveness of policies that enhance export competitiveness could be improved in these countries. The second step was to examine and differentiate the variety of industrial politics in the CEECs, with special emphasis on tools used in order to promote incoming foreign direct investment and technological development. The third step was an assessment of CEECs innovation and R&D policies, and their linkages with competitiveness, for a better understanding of future options in the CEECs. It is outside the scope of this study to formulate a new industrial policy for certain countries since there is a wide variation in the level of development, workforce structure and industrial specialization of the countries examined in this study. Making predictions that are generally applicable to all member countries of the European Union (EU) is not possible in the international economic environment of June 2013. This study highlights that there is a need for a country specific industrial policy for each member country. During the development of industrial policy, the decision makers of each country must make complex decisions which consider all past and current economic factors. It is the intention of this study to inspire deeper, new ways of thinking about industrial policies in the CEECs.
Keywords: O14; O25; L16; L50; L52; 330; Industrial policy; clusters; green growth; innovation; manufacturing; competitiveness; Central and Eastern Europe